Efektifivitas Penerapan Model Pembelajaran Kunjung Karya Berbantuan Media Serbaneka dalam Meningkatkan Keaktifan Belajar Siswa pada Mata Pelajaran PKn di Kelas IV MIN 4 Bone - Patahuddin, Muh. Husain; Dewantara, Andi Harpeni; Hasan, Hasan (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This research is motivated by the low learning activity of class IV students at MIN 4 Bone. The low learning activity is caused by the dominance of the lecture method in the learning process which causes students to be less enthusiastic or enthusiastic about Civics subjects. The learning model of visiting works assisted by various media is an alternative to stimulate student learning activeness in Civics learning. The purpose of this study was to determine the effectiveness of the visiting learning model with the help of various media in Civics subjects in increasing student learning activity. This research is quantitative research, the method used is Pre-Experimental Design with Intact-Group Comparison research design using two groups, namely the experimental group and the control group. The experimental group uses the visiting learning model with the help of various media and the control class uses a conventional learning model. Data collection techniques in this study used questionnaires and documentation. Samples were taken from students of class IV MIN 4 Bone, totaling 18 people. The sampling technique used is